2022
DOI: 10.1126/science.abq5011
|View full text |Cite
|
Sign up to set email alerts
|

Treating early postnatal circuit defect delays Huntington’s disease onset and pathology in mice

Abstract: Recent evidence has shown that even mild mutations in the Huntingtin gene that are associated with late-onset Huntington’s disease (HD) disrupt various aspects of human neurodevelopment. To determine whether these seemingly subtle early defects affect adult neural function, we investigated neural circuit physiology in newborn HD mice. During the first postnatal week, HD mice have less cortical layer 2/3 excitatory synaptic activity than wild-type mice, express fewer glutamatergic receptors, and show sensorimot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 39 publications
2
36
0
2
Order By: Relevance
“…Maybe coordinated activity patterns can even be used for targeted interventions to correct deviations from the normal developmental trajectory. Along these lines, a recent study showed that correcting developmental deficits of glutamatergic transmission in layer 2/3 of the cortex rescues electrophysiological deficits and prevents the development of symptoms in a mouse model of Huntington’s disease later in life [ 13 ].…”
Section: Gamma Oscillations and Activity-dependent Network Refinementmentioning
confidence: 99%
“…Maybe coordinated activity patterns can even be used for targeted interventions to correct deviations from the normal developmental trajectory. Along these lines, a recent study showed that correcting developmental deficits of glutamatergic transmission in layer 2/3 of the cortex rescues electrophysiological deficits and prevents the development of symptoms in a mouse model of Huntington’s disease later in life [ 13 ].…”
Section: Gamma Oscillations and Activity-dependent Network Refinementmentioning
confidence: 99%
“…Electrical activity in neurons regulates cortical development. Therefore, Braz and colleagues 4 investigated the neurophysiological characteristics of layer 2/3 somatosensory cortical neurons using whole‐cell recordings in three mouse models: Hdh Q7/Q111 mice, where the first exon of HTT is replaced by human exon 1 carrying 111 CAG repeats; HTT flox/flox mice electroporated in utero with a plasmid targeting CRE‐recombinase expression by a NeuroD promoter, therefore depleting the HTT protein in cortical neurons; and wild‐type littermates. Hdh Q7/Q111 mice had abnormal excitatory postsynaptic activity from postnatal day 1 (P1) to P3, alongside simpler dendritic arbors.…”
Section: Figurementioning
confidence: 99%
“…The transient changes present in HD mice during the early postnatal period can be prevented increasing excitatory synaptic responses with an ampakine, resulting in with posterior improvement in phenotypes and pathology in HD mice. Reproduced with permission from Braz et al 4 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Figurementioning
confidence: 99%
“…In support of this, huntingtin has been suggested to play essential roles during development, such as control of mitosis and neurogenesis [ 25 , 26 ], as well as regulation of synaptogenesis and spine structure [ 27 ]. Moreover, HD has been shown to be associated with neurodevelopmental alterations [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%